Forward Genetic Screen for Caenorhabditis elegans Mutants with a Shortened Locomotor Healthspan - Kawamura, Kazuto (G3 (Bethesda), 2019)
Two people with the same lifespan do not necessarily have the same healthspan. One person may retain locomotor and cognitive abilities until the end of life, while another person may lose them during adulthood. Unbiased searches for genes that are required to maintain locomotor ability during adulthood may uncover key regulators of locomotor healthspan. Here, we take advantage of the relatively short lifespan of the nematode Caenorhabditis elegans and develop a novel screening procedure to collect mutants with locomotor deficits that become apparent in adulthood. After ethyl methanesulfonate mutagenesis, we isolated five C. elegans mutant strains that progressively lose adult locomotor ability. In one of the mutant strains, a nonsense mutation in elpc-2, which encodes Elongator Complex Protein Component 2, causes a progressive decline in locomotor ability during adulthood. Mutants and mutations identified in the present screen may provide insights into mechanisms of age-related locomotor impairment and the maintenance of locomotor healthspan.